Organisational practices and strategy formation in South African construction firms - Pillay, Nathan (My University, 2015)
The strategic environment for construction continues to increase in complexity, and South African construction firms seem to attempt strategy formation in what is still a traditional and linear process. This research aimed to investigate organisational practices and strategy formation in South African construction firms. It is a dual-pronged approach, looking at both strategy theory and practice, which, in combination, results in strategy formation. There are two aspects to the research methodology. The theory of strategy is carried out by a literature review. Organisational practices in strategy formation are studied by qualitative research means employing in-depth open-ended questions to respondents who all are executives of large South African construction firms. The key findings provide evidence that traditional strategy planning and competitive analysis tools are no longer adequate to provide the level of understanding of complex organisations. Systems thinking was found to be an appropriate approach to complex strategic environments and strategy. Four perspectives of organisational practices were found to positively affect strategy formation, namely, leadership, configuration, strategy and decision making. Sixteen core practices go on to deepen the definition of these perspectives. Executive managers have to equip themselves with understanding systems thinking in order to repsond to the increasing complexity of the strategic environment. This competence, along with supporting practices as discussed in this report, is going to provide their organisations with a fundamental understanding of strategy formation and the resultant strategic advantage.
Keywords: Strategic planning -- South Africa. Project management -- South Africa. Leadership -- South Africa.Construction industry -- South Africa -- Management.